Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
wouldn't it be -7 and 5? I'm pretty sure that you switch the signs around.
Step-by-step explanation:
set y=0 and solve. -7 + 7 = 0 and 5 - 5 = 0. my teacher told me to switch the signs for each factored term. hope this helps.
Answer:
x = -7
x = 5
Step-by-step explanation:
Hello!
We can use the Zero Product Property to solve for the Zeroes.
Zero product Property
The zero product property stars by factoring a quadratic. You then set each of the factors to zero, and solve for the variable in the factor.
Factored form: y = a(x - h)(x - k)
- 0 = a(x - h)(x - k)
- 0 = (x - h)(x - k) Divide by a
Now, let's call each factor, A and B. To get to 0, either A, B, or both have to be 0. We prefer to solve for both.
Solve
- y = -16(x + 7)(x - 5)
- 0 = -16(x + 7)(x - 5)
- 0 = (x + 7)(x - 5) Divide by -16
- x + 7 = 0, x = -7
- x - 5 = 0, x = 5
The zeroes of the Quadratic is -7 and 5.
Why do we replace it with 0?
Zeroes means the x-intercepts, or the roots of a quadratic. An x-intercet is when y is equal to 0. So we replace y with 0, and solve for x.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.